Targeted Gene Expression Profiling of Human Myeloid Cells From Blood and Lung Compartments of Patients With Tuberculosis and Other Lung Diseases - Kotze, Leigh Ann; van der Spuy, Gian; Leonard, Bryan; Penn-Nicholson, Adam; Musvosvi, Munyaradzi; McAnda, Shirley; Malherbe, Stephanus T.; Erasmus, Mzwandile; Scriba, Thomas; Koegelenberg, Coenraad F. N.; Allwood, Brian W.; Walzl, Gerhard; et al. (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSC) have been identified in the peripheral blood and granulomas of patients with active TB disease, but their phenotype-, function-, and immunosuppressive mechanism- spectrum remains unclear. Importantly, the frequency and signaling pathways of MDSC at the site of disease is unknown with no indication how this compares to MDSC identified in peripheral blood or to those of related myeloid counterparts such as alveolar macrophages and monocytes. Most phenotypic and functional markers have been described in oncological studies but have not yet been validated in TB. Using a panel of 43 genes selected from pathways previously shown to contribute to tumour-derived MDSC, we set out to evaluate if the expression of these additional functional markers and properties may also be relevant to TB-derived MDSC. Differential expression was investigated between MDSC, alveolar macrophages and monocytes enriched from bronchoalveolar lavage fluid and peripheral blood of patients with active TB, patients with other lung diseases (OLD). Results demonstrated that anatomical compartments may drive compartment-specific immunological responses and subsequent MDSC immunosuppressive functions, demonstrated by the observation that MDSC and/or monocytes from PB alone can discriminate, via hierarchical clustering, between patients with active TB disease and OLD. Our data show that the gene expression patterns of MDSC in peripheral blood and bronchoalveolar lavage fluid do not cluster according to disease states (TB vs OLD). This suggests that MDSC from TB patients may display similar gene expression profiles to those found for MDSC in cancer, but this needs to be validated in a larger cohort. These are important observations for TB research and may provide direction for future studies aimed at repurposing and validating cancer immunotherapies for use in TB.